Analysis of Audit Planning on Financial Report Based on Time Pressure Perspective at Public Accountant of Budhananda Munidewi (Case Study at KM Institution) - IGA Kameswari; N M W D Pratiwi; K Nurhayanti (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
This research aims to analyze the conformity of financial statement audit planning based on a time pressure perspective. This research using financial statement audit planning design of Budhananda Munidewi Public Accountant Office in this case is quality control system. Data collection methods used were questionnaires, observations, interviews, and documentation techniques. The analysis technique in this research is qualitative descriptive analysis. The results of this research show that (1) the results of comparing working hours of normal time with working hours which are under time pressure say that there is a reduction in working hours taken by the auditor in completing the audit assignments which were 184 working hours to 128 working hours. (2) the comparison of the design of financial report audit planning based on the perspective of time pressure is said that there is an audit plan that is not implemented such as an audit engagement letter is not made, an audit proposal is not made so that the audit strategy is not used, and the determination of audit risk and initial materiality is not done.